Cancer profile in Central Jakarta: A 5-year descriptive study - Gondhowiardjo, Soehartati Argadikoesoema; Silalahi, Montesqieu; Manuain, Donald Arinanda; Priharto, R Koesmedi; Yekti, Widyastuti Endro (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2018)
Introduction: Global Burden of Cancer 2012 (GLOBOCAN 2012) estimated 14.1 million new cases of cancer worldwide in 2012. This data was obtained from countries that have a population-based cancer registry. Cancer registration is useful in classifying information from all cancer cases to generate statistics of cancer incidence in a particular population as well as providing a framework for interpreting and controlling the impact of cancer in the community. Indonesia has not had a population-based cancer registry currently. The Minister of Health of Indonesia has designated Dr. Cipto Mangunkusumo Hospital as a control center for cancer registration to establish a population-based cancer registry in Jakarta province.Methods: This cross-sectional descriptive study aimed to describe the cancer profile in Central Jakarta 2008-2012 based on data of RSCM as cancer registry control center in Jakarta province. The data were collected using Srikandi form, a form for cancer registry in Dr. Cipto Mangunkusumo Hospital.Result: The results obtained 1,797 cases of cancer in Central Jakarta from 2008- 2012 with male and female ratio of 1:1.9. The majority of patients came to health providers with advanced stage. The most common cancers were breast cancer, uterine cervical cancer, hematopoietic and reticuloendothelial system cancer, nasopharyngeal cancer, lung and bronchial cancer and lymph node cancer.Conclusions: This research has some similarities with data from GLOBOCAN 2012. However, it is to be noted that data showed that many patients come in an advanced stage of cancer. Moreover, some part of the research data is incomplete due to inadequacy in the filling process of Srikandi form.